1998
DOI: 10.1101/gad.12.14.2114
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β-stimulated cooperation of Smad proteins with the coactivators CBP/p300

Abstract: TGF-β and activin induce the phosphorylation and activation of Smad2 and Smad3, but how these proteins stimulate gene transcription is poorly understood. We report that TGF-β receptor phosphorylation of Smad3 promotes its interaction with the paralogous coactivators CBP and p300, whereas CBP/p300 binding to nonphosphorylated Smad3 or its oligomerization partner Smad4 is negatively regulated by Smad–intramolecular interactions. Furthermore, p300 and TGF-β receptor-phosphorylated Smad3 synergistically augment tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
342
1
7

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(368 citation statements)
references
References 34 publications
18
342
1
7
Order By: Relevance
“…The complex marked with the arrowhead was supershifted such that it was unable to enter the gel when extracts were preincubated with polyclonal antibody to Tal1 (anti-Tal1) or a monoclonal antibody to p300 (RW128) (anti-p300) but not with a monoclonal antibody to a human c-Myc epitope (9E10) (anti-Myc epitope) or Tal1 preimmune immunoglobulin (Tal1 preimmune) p300 and TAL1 transcriptional activity S Huang et al 1998). While modest from a quantitative standpoint, the magnitude of p300-stimulated coactivation was comparable to that described for BETA-2 (Mutoh et al, 1998), Smad3 (Janknecht et al, 1998), and AML1 (Kitabayashi et al, 1998). Finally, no e ect of p300 was seen in cells transfected with the reporter plasmid alone (Figure 4).…”
Section: P300 Augments Transcription Stimulated By Tal1-e12 Heterodimerssupporting
confidence: 66%
“…The complex marked with the arrowhead was supershifted such that it was unable to enter the gel when extracts were preincubated with polyclonal antibody to Tal1 (anti-Tal1) or a monoclonal antibody to p300 (RW128) (anti-p300) but not with a monoclonal antibody to a human c-Myc epitope (9E10) (anti-Myc epitope) or Tal1 preimmune immunoglobulin (Tal1 preimmune) p300 and TAL1 transcriptional activity S Huang et al 1998). While modest from a quantitative standpoint, the magnitude of p300-stimulated coactivation was comparable to that described for BETA-2 (Mutoh et al, 1998), Smad3 (Janknecht et al, 1998), and AML1 (Kitabayashi et al, 1998). Finally, no e ect of p300 was seen in cells transfected with the reporter plasmid alone (Figure 4).…”
Section: P300 Augments Transcription Stimulated By Tal1-e12 Heterodimerssupporting
confidence: 66%
“…Co-transfection with p300 increased the level of Cited2 co-immunoprecipitated with Flag-tagged Smad3 (Figure 3a), indicating that p300 enhances the interaction between Cited2 and Smad3. It has been shown that p300 is important for Smad-mediated transcription Janknecht et al, 1998;Nishihara et al, 1998;Topper et al, 1998). Transfection of HEK293T cells with p300 alone modestly enhanced Smad3-mediated transcription of SBE4-Luc (Figure 3b).…”
Section: Cited2 Interacts With Smads 2 Andmentioning
confidence: 90%
“…These complexes are translocated into the nucleus and interact with a variety of transcription factors, such as AP-1, Sp1, FAST, ATF-3, TFE-3, nuclear receptors and E2F4/5, leading to activation or suppression of transcription (ten Dijke et al, 2000;Zimmerman and Padgett, 2000;Shi and Massague, 2003). In addition to DNA-binding transcription factors, the co-activator function of CBP/p300 is essential for Smad-mediated transcription Janknecht et al, 1998;Nishihara et al, 1998;Topper et al, 1998). The profile of Smad-binding cofactors during development or under various growth conditions determines cellular responses to TGF-b (Massague, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Smad2 and -3 are R-Smads activated by TGF-b and activin receptors, whereas Smad1, -5 and -8 are activated by BMP receptors. In the nucleus, the Smad oligomers recruit the transcriptional co-activators p300/ CBP (Feng et al, 1998;Janknecht et al, 1998;Nishihara et al, 1998;Itoh et al, 2000). p300 and CBP are structurally related proteins with histone acetyltransferase (HAT) activity.…”
Section: Introductionmentioning
confidence: 99%